Wood growth of Tabebuia barbata (E. Mey.) Sandwith (Bignoniaceae) and Vatairea guianensis Aubl. (Fabaceae) in Central Amazonian black-water (igapó) and white-water (várzea) floodplain forests - Fonseca Júnior, Sinomar Ferreira da; Piedade, Maria Teresa Fernandez; Schöngart, Jochen (Trees - Structure and Function, 2009)
Tree growth is a fundamental indicator for conservation plans of Amazonian floodplain forests. In this study we use dendrochronology to analyze wood growth patterns of Tabebuia barbata and Vatairea guianensis, two tree species occurring in nutrient-rich white-water (várzea, Mamirauá Sustainable Development Reserve, MSDR) and nutrient-poor black-water (igapó, Amanã Sustainable Development Reserve, ASDR) floodplain forests of Central Amazonia. From 20 trees per species and floodplain system (total of 80 trees) growing under a similar flooding regime with a mean inundation height of about 4 m we measured diameter at breast height (dbh). We sampled two cores per tree with an increment corer at the height of dbh to determine wood density (WD), tree age and mean radial increment (MRI) rates. The wood samples were macroscopically analyzed. Both tree species show distinct annual tree rings characterized by marginal parenchyma tissues. MRI was measured by a digital measuring device and WD was determined by the ratio dry mass/fresh volume. MRI of both tree species was significantly higher in the várzea than in the igapó, which can be traced back to the contrasting nutrient status. WD showed no difference comparing both floodplain forest types. Tree ages of a species for the same diameter are more than twofold higher in the igapó than in the várzea. To insure a sustainable harvest, felling cycles in these forests should be adjusted according to rates of growth.
Keywords: Climatology; Forestry; Growth (materials); Nutrients; Planning; Strategic Planning; Sustainable Development; Wood; Amazon; Conservation; Dendrochronology; Floodplain Forest; Forest Management; Banks (bodies Of Water); Conservation; Forest Management; Forestry; Forests; Growth; Meteorology; Nutrients; Planning; Wood; Bignoniaceae; Fabaceae; Orithyia (angiosperm); Tabebuia; Vatairea